AN INVESTIGATION ON READING HABIT AND ATTITUDE TOWARD READING AMONG JUNIOR HIGH SCHOOL STUDENTS - Ninda Chairanissa, - (2018)
This study was aimed to investigate reading habit and attitude toward reading among junior high school students. This study implemented a case study design involving ten students at one junior high school in West Bandung Regency as participants. The data collections were obtained from classroom observation, questionnaire, interview, home visit, and document. This study revealed that the students lacked proper reading habit. The students preferred watching TV and surfing the internet than reading for their leisure time. Most of them read-only for 1-2 hours per day. In terms of reading material preference, most of students preferred fiction books written in Indonesian language. Regarding the attitude toward reading, students had overall negative reading attitude. It was shown by their lack of motivation and enjoyment in reading activity. Then, the students faced difficulty due to their anxiety in reading English activity. Moreover, the home visit paid to three students indicated that family literacy environment gave low stimulation to good reading habit. The study invites teachers, school authorities, and family members to team up to improve students' reading habit.